2019
DOI: 10.1111/joim.12985
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation is frequent but does not affect risk stratification in pulmonary embolism

Abstract: BackgroundAlthough prior studies indicate a high prevalence of atrial fibrillation (AF) in patients with pulmonary embolism (PE), the exact prevalence and prognostic impact are unknown.MethodsWe aimed to investigate the prevalence, risk factors and prognostic impact of AF on risk stratification, in‐hospital adverse outcomes and mortality in 528 consecutive PE patients enrolled in a single‐centre registry between 09/2008 and 09/2017.ResultsOverall, 52 patients (9.8%) had known AF and 57 (10.8%) presented with A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Ebner et al reported that AF on admission with PE 1-year mortality was 17.5%, and it do not affect the prognostic performance. 20 However, they neither distinguished whether AF was subsequent or existed before, nor it was persistent or paroxysmal. In addition, Ng et al showed that subsequent AF with PE 6-month mortality was 10%, 19 while they did not investigate the effects of different AF types on the mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ebner et al reported that AF on admission with PE 1-year mortality was 17.5%, and it do not affect the prognostic performance. 20 However, they neither distinguished whether AF was subsequent or existed before, nor it was persistent or paroxysmal. In addition, Ng et al showed that subsequent AF with PE 6-month mortality was 10%, 19 while they did not investigate the effects of different AF types on the mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported age, congestive heart failure as independent predictors for subsequent AF in PE cohort. [19][20][21] Massive PE, which causes a sharp increase in afterload and stretch injuries, could also be associated with AF. Our study confirmed that massive PE was a risk factor for new-onset AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent cohort study, it was found that AF did not affect risk stratification in PE. 28 The patients with AF on admission had adverse in-hospital outcome in 8.8% compared with those in sinus rhythm (8.3%, p ¼ 0.80). The adverse in-hospital outcome in the patients with newly diagnosed AF 3/34 (8.8%) was not significantly different from those without AF 36/442 (8.1%) or those with known AF 5/52 (9.6%).…”
Section: Discussionmentioning
confidence: 93%
“…As the author discussed, the prognostic value of AF in acute PE was likely to be small rather than absent. 28 A larger sample size study might have yielded statistically significant differences. In a study based on National Inpatients Sample database in the United States, 201,360 patients with PE were analyzed.…”
Section: Discussionmentioning
confidence: 99%